Children’s Preparedness through Disaster Response Training in Sentra of Drama TKIT Baitussalam 2 Cangkringan Sleman - Cahyani, Widia Arinta; Windiarti, Rina (BELIA: Early Childhood Education Papers, 2017)
A disaster is an event that can happen anywhere, anytime and overwrite anyone. For it is necessary preparation for the community in the area of disaster-prone to know what things to do in facing disaster. This study aims to measure the level of disaster preparedness in children through disaster response training in drama centers TKIT Baitussalam 2 Cangkringan Sleman. Through disaster response training, it can be known whether or not there is a difference in the level of preparedness of children.The method used in this study is experimental. Research using one group pretest posstest design that experiments conducted in a single group without a comparison group. The research instrument with preparedness parameter is using Guttman scale with a straight answer "Yes" and "No".The population in this study are all children in TKIT Baitussalam 2 Cangkringan totaling 138. The sample in this research is class of B2 which amounted to 28. The sampling techniques used in this research is Purporsive sampling. Data analysis techniques used in this research is descriptive analysis, normality test and inferensial test with Paired Sample t-Test.Test the hypothesis States that Ha is received and Ho is rejected. The calculation results of Paired t-test between pretest and posttest experimental groups with a value of thitung =-41,086 and the sig (2-tailed) < 0.05. The average rating on stage initially 9.04 pretest became 24.86 posttest, so there is a significant difference between the preparedness of children before and after disaster response training.